2016
DOI: 10.1155/2016/9503652
|View full text |Cite
|
Sign up to set email alerts
|

Immune Signatures in Patients with Psoriasis Vulgaris of Blood‐Heat Syndrome: A Systematic Review and Meta‐Analysis

Abstract: Objective. To determine whether immunological serum markers IFN-γ, IL-4, IL-17, IL-23, IL-6, TNF-α, and IL-10 are elevated or decreased in patients compared with healthy controls. Methods. A complete search of the literature on this topic within the past 30 years was conducted across seven databases. Seventeen studies including 768 individuals were identified. Differences in serum marker levels between subjects and controls were pooled as MDs using the random-effects model. Results. The pooled MDs were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…We therefore considered JYG as a safe and effective medication for the treatment of psoriasis. Results from a pooled analysis conducted by us also indicated that levels of IFN-γ, IL-17, IL-23, and TNF-α were significantly increased, whereas those of IL-4 and IL-10 were significantly decreased in the sera of patients with blood-heat syndrome of psoriasis [43]. Determining the effect of the JY prescription on the aforementioned immune factors will be a focus area of our future research.…”
Section: Discussionmentioning
confidence: 87%
“…We therefore considered JYG as a safe and effective medication for the treatment of psoriasis. Results from a pooled analysis conducted by us also indicated that levels of IFN-γ, IL-17, IL-23, and TNF-α were significantly increased, whereas those of IL-4 and IL-10 were significantly decreased in the sera of patients with blood-heat syndrome of psoriasis [43]. Determining the effect of the JY prescription on the aforementioned immune factors will be a focus area of our future research.…”
Section: Discussionmentioning
confidence: 87%
“…We therefore considered JYG as a safe and effective medication for the treatment of psoriasis. Results from a pooled analysis conducted by us also indicated that levels of interferon-γ, IL-17, IL-23, and tumor necrosis factor-α were significantly increased, whereas those of IL-4 and IL-10 were significantly decreased in the sera of patients with blood-heat syndrome of psoriasis [42]. Determining the effect of the JY prescription on the aforementioned immune factors will be a focus area of our future research.…”
Section: Discussionmentioning
confidence: 87%
“…The prevalence of psoriasis in the United States is about 3% [115] and is considered a major public health problem due to ineffective long-term treatments that resulted in an estimated economic burden amounting to $11 billion in 2013. [116,117] Recent studies on the pathogenesis of psoriasis have revealed not only a genetic component, [118] but also immune dysfunction, [119] as evidenced by an imbalance in resident and infiltrating skin immune cells, including dendritic cells, macrophages [41] and MC. [3,14,19,91,120] Our findings reveal that TNF stimulates KC proinflammatory mediator secretion via mTOR activation.…”
Section: Resultsmentioning
confidence: 99%